Innervation of the substantia nigra - Misgeld, Ulrich (Cell & tissue research, 2004)
This review describes inputs to neurons in the substantia nigra and contrasts them with the action of agonists for the putative receptors through which they act. Special emphasis is placed on gamma-aminobutyric acid (GABA) afferents. Dopamine released from the somato-dendritic compartment of dopamine neurons and endocannabinoids released from dopamine and GABA neurons serve as retrograde signals to modulate GABA release. The release may be fostered by Ca2+ release from intracellular Ca2+ stores, which in turn may be influenced by the inputs.
Gesehen am 08.04.2021